Information Mismatch: Cancer Risk Counseling with Diverse Underserved Patients. Issue 5 (13th March 2017) - Joseph, Galen; Pasick, Rena J.; Schillinger, Dean; Luce, Judith; Guerra, Claudia; Cheng, Janice Ka Yan
Abstract: As genetics and genomics become part of mainstream Medicine, these advances have the potential to reduce or exacerbate health disparities. Gaps in effective communication (where all parties share the same meaning) are widely recognized as a major contributor to health disparities. The purpose of this study was to examine GC‐patient communication in real time, to assess its effectiveness from the patient perspective, and then to pilot intervention strategies to improve the communication. We observed 64 English‐, 35 Spanish‐ and 25 Chinese‐speaking ( n = 124) public hospital patients and 10 GCs in 170 GC appointments, and interviewed 49 patients who were offered testing using the audio recordings to stimulate recall and probe specific aspects of the communication. Data analyses were conducted using grounded theory methods and revealed a fundamental mismatch between the information provided by GCs and the information desired and meaningful to patients. Several components of the communication that contributed to this mismatch and often resulted in ineffective communication included: (1) too much information; (2) complex terminology and conceptually difficult presentation of information; (3) information perceived as not relevant by the patient; (4) unintentional inhibition of patient engagement and question‐asking; (5) vague discussions of screening and prevention recommendations. Our findings indicate a need to transform the standard model of genetic counseling communication using evidence‐based principles and strategies from other fields of Medicine. The high rates of limited health literacy in the US, increasing access of diverse populations to genetic services, and growing complexity of genetic information have created a perfect storm. If not directly addressed, this convergence is likely to exacerbate health disparities in the genomic age.